ENGLISH LANGUAGE ACQUISITION VIA DUOLINGO APPLICATION: EFFECTIVITY AND CHALLENGES - Liann Camille Davalos Perez (Lingua Pedagogia, 2022)
English Language acquisition is significant as education enters globalization. English is the world’s lingua franca which enables speakers with different language backgrounds to communicate effectively. In order to successfully teach the language, teachers use different tools and approaches. 21st-century education opens a new effective way of conducting the learning process. It upgrades from a conventional type into ICT (Information and Communication Technology) integrated one which might accommodate full-online English Learning. Duolingo is a language-learning application wherein students can learn English from a series of activities like Translation, Matching, Dictation, Fill-in-the-blank, Speaking, Listening, Multiple Choice, and Competition. Thus, this paper discussed the use of Duolingo in language learning and its capacity to accommodate full English acquisition. Various challenges arose about its usage like - Unavailability of Devices, Internet Access, Students’ Behavior while using Phones, and Activity problems in Duolingo - unnatural sentences, lack of grammar guide, weak translations, pronunciation errors, and annoying advertisements which made Duolingo’s effectiveness questionable.  As a result, this paper found out that Duolingo may just be a supporting tool in teaching the basics, and it is not enough to accommodate full-English language learning. However, as the application upgrades, further researches must be conducted to gather changes.